Sebaran Kualitas Air Laut di Perairan Sekitar PLTU Teluk Sepang Kota Bengkulu Berdasarkan Parameter Fisika-Kimia - Lizalidiawati Lizalidiawati; Erma Juniarti; Budi Harlianto (Newton-Maxwell Journal of Physics, 2021)
PLTU Teluk Sepang Bengkulu City produces heat waste dumped back into the sea which affects the quality of the water so that it has a negative impact on marine life. This study aimed to identify the quality of the water around PLTU Teluk Sepang Bengkulu City based on the physical and chemical parameters. The method used was direct measurement at the research location which is carried out at 12 measurement points,i.e 4 points around the outlet area, and 8 points in the off-shore area. The measurement result was compared with seawater quality standard for marine biota based on the Minister of Environment Decree No. 51 of 2004 and was validated by analysis of sea water quality before the PLTU had operated. The result showed that the some parameters met the quality standards for marine biota included DO of 5.62-7.82, pH and turbidity in the offshore area with each value of 7.24-7.86 and 1.68-4.846 NTU. Meanwhile, the parameters which did not meet quality standards include a temperature of 30.62-36 ºC, a salinity of 26.6-30 ‰,  pH and turbidity around the outlet area with each value of  6.7-6.88 and 23.25-146.8 NTU. Based on the validation result, it showed that heat waste had a very significant effect on the physical and chemical parameters of the waters, especially on temperature, pH, and turbidity.